Case Report: Rapid resolution of malignant acanthosis nigricans following chemotherapy for cervical cancer - Hu, Min; Chen, Xiangrui; Tong, Xiaobo; Hao, Chengluo; Han, Yunwei (Frontiers in Oncology, 2025)
We present a 55-year-old non-obese female exhibiting rapidly progressive malignant acanthosis nigricans (MAN) as the initial manifestation, characterized by widespread malodorous skin lesions that preceded the eventual diagnosis of human papillomavirus 16 (HPV16)-positive, poorly differentiated cervical squamous cell carcinoma by four years. Following chemotherapy, both tumor markers and cutaneous manifestations demonstrated rapid regression. However, at the most recent follow-up (August 2025), the patient was hospitalized for management of grade 3 myelosuppression and a secondary pulmonary infection, necessitating temporary suspension of antitumor therapy. This treatment–response correlation provides compelling clinical substantiation for the “tumor-secretory factor-driven” pathogenesis, indicating that MAN may serve as a critical early paraneoplastic signal of HPV-associated gynecologic malignancies and warrant prompt systemic screening upon its recognition.